Superhero HARRY : The Runaway Robot - Ruiz, Rachel (Rachel Marie); May, Steve (North Mankato, Minnesota : Picture Window Books, a Capstone imprint, 2018)
Harry's latest invention--a Superhero Robot programmed to do chores--malfunctions, and the robot goes out of control, creating chaos at school.
Keywords: Robots -- Juvenile fiction; Superheroes -- Juvenile fiction